Advancing the path to in-vivo imaging in freely moving mice via multimode-multicore fiber based holographic endoscopy - Du, Yang; Dylda, Evelyn; Stibůrek, Miroslav; Gomes, André D; Turtaev, Sergey; Pakan, Janelle M P; Čižmár, Tomáš (Neurophotonics, 2024)
SIGNIFICANCE: Hair-thin multimode optical fiber-based holographic endoscopes have gained considerable interest in modern neuroscience for their ability to achieve cellular and even subcellular resolution during in-vivo deep brain imaging. However, the application of multimode fibers in freely moving animals presents a persistent challenge as it is difficult to maintain optimal imaging performance while the fiber undergoes deformations. AIM: We propose a fiber solution for challenging in-vivo applications with the capability of deep brain high spatial resolution imaging and neuronal activity monitoring in anesthetized as well as awake behaving mice. APPROACH: We used our previously developed M3CF multimode-multicore fiber to record fluorescently labeled neurons in anesthetized mice. Our M3CF exhibits a cascaded refractive index structure, enabling two distinct regimes of light transport that imitate either a multimode or a multicore fiber. The M3CF has been specifically designed for use in the initial phase of an in-vivo experiment, allowing for the navigation of the endoscope's distal end toward the targeted brain structure. The multicore regime enables the transfer of light to and from each individual neuron within the field of view. For chronic experiments in awake behaving mice, it is crucial to allow for disconnecting the fiber and the animal between experiments. Therefore, we provide here an effective solution and establish a protocol for reconnection of two segments of M3CF with hexagonally arranged corelets. RESULTS: We successfully utilized the M3CF to image neurons in anaesthetized transgenic mice expressing enhanced green fluorescent protein. Additionally, we compared imaging results obtained with the M3CF with larger numerical aperture (NA) fibers in fixed whole-brain tissue. CONCLUSIONS: This study focuses on addressing challenges and providing insights into the use of multimode-multicore fibers as imaging solutions for in-vivo applications. We suggest that the upcoming version of the M3CF increases the overall NA between the two cladding layers to allow for access to high resolution spatial imaging. As the NA increases in the multimode regime, the fiber diameter and ring structure must be reduced to minimize the computational burden and invasiveness.
Keywords: freely moving; multimode fiber; in-vivo imaging; fiber connection; multicore fiber; holographic endoscopy